Optical properties of individual CdS/CdSe/CdS nanocrystals: spherical quantum wells as single-photon sources. (2nd July 2022) - Allemand, A; Kulzer, F; Mahler, B; Dujardin, C; Houel, J
Abstract: We have synthesized CdS(1.3 nm)/CdSe(1.7 nm)/CdS(3.4 nm) spherical quantum wells (SQWs) with a diameter of 13 nm and demonstrated the first photon-antibunching from their emission, labelling them as single-photon sources. Antibunching survives even at high excitation intensities, ruling-out strong emission from the bi-exciton. For the largest intensities, antibunching coupled to spectral measurements reveal the signature of a blue-shifted emission, associated to an irreversible photo-aging effect. A statistical analysis over 26 SQWs demonstrates a moderate correlation between the energy of the main and the blue-shifted emission. Intensity-timetraces recorded on 28 single SQWs show weak blinking, with a median time spent in the bright state of 89%. Their emission decay reveals a complex dynamic with either three or four exponential components. We assigned three of them to the neutral and singly-charged excitons and the slowest to defect emission. While SQWs have been initially designed for laser-oriented applications, we demonstrate that they can serve as efficient single-photon sources.